Interdiffusion coefficients of binary multiphase systems with consideration of variation in Molar volumes - Li, J.F.; Agyakwa, Pearl; Johnson, Christopher Mark (Pushpa Publishing, 2014)
This communication introduces a modification to the Wagner method to reveal and correct considerable systematic errors existing in the previously established analytical methods used to calculate the interdiffusion coefficients of binary multiphase systems where all the phases have narrow homogeneity ranges and there are step changes of concentration and/or Molar fraction at the interfaces of the different phases.